Penguatan Manajemen Waktu dan Work-Life Balance bagi Kepala Sekolah dalam Meningkatkan Efikasi Diri - Anwar, Saiful; Utaminingsih, Sri; Indayani, Rin (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service is an implementation of research that has been previously conducted by the Community Service team entitled Factors Affecting Professional Commitment. As is commonly known, self-efficacy is a form of organizational behavior that builds the performance of a principal. In addition to being able to increase the professional commitment of the principal, in theory self-efficacy is believed to be able to improve the performance of the principal. This community service program aims to strengthen time management and work-life balance for principals through a workshop and experiential learning approach in order to increase their self-efficacy in carrying out leadership tasks optimally. This PKM is present in the environment of the association of private high school principals in Tangerang City. The output targets to be achieved from this program include increasing the self-efficacy of the principal, as well as publication of activity results in the form of scientific articles or community service journals. With this program, it is hoped that principals can develop healthier and more effective work patterns, which have a positive impact on their personal well-being and professional performance in leading schools. Keywords: Self-Efficacy, Time Management, Work-Life Balance, Principal